1.
2.
3.
Returning to differentiation after a fairly long break and presented with three questions. I'm sure there's a simpler way to do them, but I can't figure it out?
1. y(x) = ln[(f(x)+g(x))^2] => y(x) = ln[(u)^2]
y'(x) = 1*[2(f'(x)+g'(x))] / (f(x)+g(x))^2
2. y(x) = ln(x^a + zx)/(e^x*e^z)
y(x) = ln (u)/(v)
y'(x) = (V) / (U) * (V)(U') / (U)(V')
y'(x) = (V)(U)(V') / (U)(V)(U')
If that makes sense?
3. y(x) = f(g(x).u(z))
y'(x) = (g(x).u(z)).(g'(x))
Sorry if this seems a bit retarded, I'm finding the textbook a bit lacklustre in parts (Chiang / Wainwright) and statistics is much more my forte!